Pengertian Dan Sumber Ajaran Islam: Dalam Lingkup Metodologi Studi Islam - Radika Mulana Yusuf; Mawar Pramestia; Ripan; Maftuh Ajma’in (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2026)
This study aims to examine the definition and sources of Islamic teachings within the framework of Islamic studies methodology in a comprehensive manner. The research employs a qualitative literature review approach to analyze Islam from both etymological and terminological perspectives, as well as to explore its epistemological foundations. The findings indicate that, linguistically, Islam conveys meanings of submission, peace, and salvation, while terminologically it is understood as a revealed religion centered on the concept of monotheism (tawhid) that governs all aspects of human life. Within the methodology of Islamic studies, the primary sources of Islamic teachings consist of the Qur’an as the absolute divine revelation, the Sunnah as the explanatory and practical authority, and ijtihad as a rational instrument that enables the teachings of Islam to remain dynamic and contextually relevant. These three sources form an integrated system of knowledge that harmonizes revelation and reason, allowing Islam to address the evolving challenges of human life. Therefore, understanding the definition and sources of Islamic teachings is not only conceptual but also methodological, playing a crucial role in the development of critical, contextual, and relevant Islamic studies.